The Difficulties Faced by the Sixth Semester Student of English Department of FKIP UKI Toraja in Translating Indonesian Text into English Text - Yizrel Nani Sallata (Teaching English as a Foreign Language Overseas Journal, 2019)
The aim of the research is to find out the difficulties faced by the sixth semester students in translating Indonesian text into English text. The writer used qualitative descriptive method to explore the objective of the research. To collect the data the writer used several steps: giving the test for the students, identifying and classifying the students' difficulties in translation. The finding showed that the students faced many difficulties: there are four kinds of difficulties categories of the translation: lexical equivalent, lexical adjustment, grammatical adjustment and grammatical equivalent. students faced two lexical and two grammatical problems in translating text from the source language into the target language where most of the students translated the sentences from the source language into target language directly that they did not pay attention on the context